MODEL PEMBANGUNAN BERBASIS MASYARAKAT DALAM PROGRAM DESA MANDIRI: STUDI KASUS - Aris Sarjito (Fakultas Politik Pemerintahan, 2025)
The Village Independent Program (VIP) is a community-based rural development model aimed at fostering self-sufficiency and economic resilience in rural communities. This research analyzes the effectiveness of the program by examining community engagement, governance structures, and sustainability factors through a qualitative case study approach using secondary data. Data sources include government reports, academic literature, and NGO case studies, which were analyzed using thematic and comparative analysis. The findings highlight that active community participation and transparent governance significantly impact program success. Villages with strong leadership, financial accountability, and diversified economic activities show higher levels of sustainability. However, challenges such as resource disparities, governance inconsistencies, and digital infrastructure limitations hinder program implementation in certain regions. The study suggests that policy improvements, digital transformation, and public-private partnerships are essential for enhancing long-term rural development outcomes. Strengthening financial transparency, expanding internet access, and fostering youth entrepreneurship are recommended to sustain the program’s impact. This research contributes to the broader discussion on scalable community-based development models, emphasizing the importance of local governance, digital inclusivity, and long-term economic planning. Keywords: community-based development, digital transformation, economic resilience, governance, rural sustainability